Pengaruh Penggunaan Metode Penemuan Terbimbing Terhadap Prestasi Belajar Matematika Siswa Pada Kelas VII SMP Negeri 18 Buton - Maya Nurlita; Azis Azis; Wa Ode Wina Desliana (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
Objective of this research was to know the effect of guided discovery method on students’ Mathematics learning achievement at grade VII of SMP Negeri 18 Buton. This research was quantitative research with experimental method and using guided discovery method. Population in this research was all students at grade VII of SMP Negeri 18 Buton. Sample of this research was taken with using purposive sampling technique that was class VII4 as an experimental class and VII3 as a control class. Data collection technique in this research was using test. Outcomes of this research obtained: 1) the average of students’ Mathematics learning outcomes on the initial test in both the control class and the experimental class were respectively 51.07 and 47.36. while the average of students’ Mathematics learning outcomes on the final test of the control class and the experimental class was 69.14 and 67.29. 2) based on the result of hypothesis test with t test obtained the value of tcount = 0.676 and the value of ttable = 1.70562. When compared tcount with ttable so tcount < ttable sig (2-tailed) 0.0505 > 0.05, so that H0 was accepted and H1 was rejected. So, it could be concluded that there was no effect significantly on Mathematics learning outcomes wth student who got learning with guided discovery method and student who got conventional learning. So, it could be said that there was no effect between learning with guided discovery method or it could be said that the application of the guided discovery method was not effective in learning in terms of students’ Mathematics learning achievement at grade VII of SMP Negeri 18 Buton.